Sea Ice CO2 Dynamics Across Seasons: Impact of Processes at the Interfaces. Issue 6 (3rd June 2020) - Van der Linden, F. C.; Tison, J.‐L.; Champenois, W.; Moreau, S.; Carnat, G.; Kotovitch, M.; Fripiat, F.; Deman, F.; Roukaerts, A.; Dehairs, F.; Wauthy, S.; Lourenço, A.; et al.
Abstract: Winter to summer CO2 dynamics within landfast sea ice in McMurdo Sound (Antarctica) were investigated using bulk ice pCO2 measurements, air‐snow‐ice CO2 fluxes, dissolved inorganic carbon (DIC), total alkalinity (TA), and ikaite saturation state. Our results suggest depth‐dependent biotic and abiotic controls that led us to discriminate the ice column in three layers. At the surface, winter pCO2 supersaturation drove CO2 release to the atmosphere while spring‐summer pCO2 undersaturation led to CO2 uptake most of the time. CO2 fluxes showed a diel pattern superimposed upon this seasonal pattern which was potentially assigned to either ice skin freeze‐thaw cycles or diel changes in net community production. In the ice interior, the pCO2 decrease across the season was driven by physical processes, mainly independent of the autotrophic and heterotrophic phases. Bottom sea ice was characterized by a massive biomass build‐up counterintuitively associated with transient heterotrophic activity and nitrate plus nitrite accumulation. This inconsistency is likely related to the formation of a biofilm. This biofilm hosts both autotrophic and heterotrophic activities at the bottom of the ice during spring and may promote calcium carbonate precipitation. Plain Language Summary: Sea ice participates actively in the regional cycling of CO2 both as a source and a sink at different times of the year depending on ice physics, ice chemistry, and ice trophic status (autotrophic vs. heterotrophic). We identified the key processes driving the CO2 dynamics in each sea ice layer (surface, interior, and bottom) from McMurdo Sound (Antarctica) from late winter to summer. At the surface, CO2 release from the ice to the atmosphere occurred in late winter while CO2 uptake occurred in summer. Superimposed upon this seasonal pattern, we observed a diurnal pattern with both release and uptake occurring over 24 hr period. This diurnal pattern can be related to physical processes (nocturnal freeze‐up and diurnal melting) or biotic processes (autotrophy or heterotrophy). In the ice interior, a succession of autotrophic and heterotrophic phases took place. At the sea ice bottom, a particular assemblage of microbial cells and organic matter, called biofilm, enabled the accumulation of biomass and nitrate plus nitrite simultaneously leading to both autotrophic and heterotrophic activities. In addition, this biofilm is suggested to promote calcium carbonate precipitation. Key Points: First long‐term monitoring of both pCO2 and CO2 fluxes at sea ice interfaces in McMurdo Sound (Antarctica) from late winter to summer Large biomass build‐up is strikingly associated with transient heterotrophy and nitrate plus nitrite accumulation New conceptual approach involving biofilm formation can explain observed inconsistencies: accumulation of nitrate plus nitrite and CaCO3